Uma proposta de sequência de jogos de química para estudantes com transtorno do espectro autista - Godoy, Tatiane Bianquini de (2023)
Games in chemistry teaching are important tools that can contribute to the teaching-learning processes due to their ability to stimulate the development of cognitive and creative aspects and also to enable the construction of knowledge in a more pleasurable way. The ludic can make teaching more meaningful both for students who are the target of special education (such as those with autism spectrum disorder, known by the acronym TEA), and for any other, helping in the teaching-learning process. Games provide a more pleasant and interesting way of learning, since playing is an essential activity for the development of the individual, as the lack of motivation combined with the difficulty that some disciplines bring, end up labeling the subject as chemistry and that is the main cause of students' disinterest. Thus, this exploratory research lists important points for the development of games in chemistry teaching for students with ASD. Based on information constituted by a bibliographical survey and systematized by Content Analysis techniques, this work observed two points: the need to discuss the role of games as a teaching and learning methodology and the lack of games in teaching chemistry for education. especially in observation for autism. Based on the constituted information, the result was the development of a sequence of five games for the 1st year of high school entitled: " Bingo of Periodic Table (bingo game), "Find the Electronic Distribution" (memory game), “Ionic-Covalent Chemical Bonds” (board game) and, finally, “Pig of Acids and Bases” (card game). The games were submitted for evaluation by specialists in the area of exact sciences and special education. With the analysis, it was possible to notice that in all the games there were doubts about its application for the target audience, which are the autistic people, showing that it may be necessary for the games to be performed in pairs and that they have the mediation of the teacher. Its development demands a more in-depth study, as the autistic public needs specific tools, not to mention that each degree of the spectrum has a different conception. The development of games for this audience, however challenging it may be, is necessary. From this, a deeper study of the degrees of autism is necessary, culminating, thus, in the creation of specific criteria for each degree in the elaboration of the games.